Financial Management in selected Public Enterprises of Haryana - Nagpal, V.P. (Gyan Management Journal, 2007)
In order to curb the evils of monopoly, concentration of economic power and wealth, the govt. had to enter into the field of production and distribution of essential goods and services. The present study is of selected state enterprises regarding their financial management and how the mismanagement of funds has been responsible for their financial failures. Finally to suggest measure for the possible effective utilization of funds of Haryana State Public Undertakings. Out of 16 units registered under companies has been taken for detailed empirical study, which forms 50%. The sample consists of 3 major types of state undertaking (i) Manufacturing (ii) Trading (iii) Servicing The research methodology include use of secondary data and the emphasis is more on the analysis and interpretation of the existing available information.